Development and validation of a quantitative real-time PCR assay for the enumeration of Clostridium sporogenes in NaCl- and nitrite-reduced meat products - Natalie Schuller; Antonia Kreitlow; Madeleine Plötz; Darleen Röpper; Amir Abdulmawjood (PLoS ONE, 2025)
In the interest of enhancing consumer health and limiting the risks associated with excessive salt consumption and nitrosamine intake, there is an ongoing initiative to reduce the use of salt and nitrite in meat products. Since important microbial barriers are compromised in their capacity to function effectively, NaCl- and nitrite-reduced products also run the risk of increasing the growth of potentially pathogenic microorganisms, such as Clostridium botulinum . In consideration of the necessity to investigate the growth behaviour of the pathogen in sodium chloride (NaCl) – and nitrite-reduced meat products in future challenge tests, a real-time PCR assay was developed and validated for the qualitative and quantitative detection of the C. botulinum surrogate Clostridium sporogenes . The quantitative polymerase chain reaction (qPCR) method based on the pelF gene showed a specifity of 100% when tested with bacterial strains of the target species and relevant non-target species. The detection limits in artificially contaminated raw sausages were 8.6 cfu per reaction and 430 cfu/g. The validation of the newly established TaqMan qPCR assay was conducted while investigating the impact of the ripening process and long-term storage of raw sausage with different salt and nitrite contents on the growth of C. sporogenes . The qPCR results were then compared to those of classic cultivation, serving as the reference method for validation. In summary the results of the qPCR showed a good correlation with those of the cultural method for the simulated conditions. However cell counts after ripening were slightly higher, when measured using qPCR. This study presents the successful implementation of a qPCR method for the detection of C. sporogenes in raw sausage and offers a significant opportunity for further research that is required in order to determine the possibilities of reducing salt and nitrite in meat products.